The business of women : marriage, family, and entrepreneurship in British Columbia 1901-51 - Buddle, Melanie, 1971- (UBC Press, 2010)
"Buddle offers a unique and important contribution to Canadian history She seeks not only to incorporate women into the history of business but also to reconceptualize business history itself by asking new questions about gender, business, and the family. Business history needs to undergo a gender "revolution." This book will promote such rethinking of the field" "Throughout history, Western women have inhabited a conceptual space divorced from the world of business. But women have always engaged in business. Who were these women, and how were they able to justify their work of those women who embraced British Columbia's frontier ethos in the early twentieth century. In this detailed examination of case studies and quantitative sources, Buddle reveals that, contrary to expectation, the typical businesswoman was not unmarried or particularly rebelious but a woman reconciling her enterpreneurship with her identity as a wife, mother, or widow. This groundbreaking study not only incorporates women into the history of business, it challenges commonly held benefits about women, business and the marriage between the two."--BOOK JACKET.